Vocational High School Students’ Difficulties in Practicing Speaking - Aryani, Farida; Romadlon, Farid Noor; Nurcahyo, Agung Dwi (Universitas Muria Kudus, 2025)
English is becoming essential in this quickly changing world because it is crucial for practically every aspect of life, especially communication. Speaking skills is a foundation for being able to communicate in English. However, many students still find it challenging to practice speaking English because it is not the mother tongue in Indonesia. This study investigated students' difficulties and the factors that cause them in English speaking practice. 80 students of Grade 10 Accounting students at SMK PGRI 2 Kudus were the participants in this study. A qualitative method was applied and the data of this study were collected through questionnaires and in-depth interviews. The questionnaire results revealed that students have difficulties in English practice; inhibition, nothing to say, low participation, and mother tongue use with